Design and analysis of vortex generator for UMP HEV using CFD - Wan Mohd Suhaimi, Wan A. Bakar (2007)
This thesis is doing vortex generator model with new high to overcome unstable airflow problem in rear car parts. So, with addition vortex generator on rear parts of proton iswara type Hybrid Electrical Vehicle (HEY) will decrease instability air movement on rear car parts. Beside that, addition of vortex generator in rear roof of car is to decrease high pressure and zero velocity area. It is because to make stability of car.Design of vortex generator is done based on shape Proton Iswara vortex generator but only with different high. The vortex generator high is determined based on this study. In this study, 3 velocities (90,100 and 110 km/h) will analyze using cosmosfioworks. Each velocity of car model will analyze with and without vortex generator. Based on this study, addition of vortex generator on rear car able to decrease total area of high pressure and low or zero velocity. This can be seen with decreasing of airflow in the rear car. It is because the vortex generator can be reduce the turbulent boundary layer flow.